A comparative study on the Iraqi special tribunal and other international trials for charges of crimes against humanity / Hadi Mukhlis Khairulmaini, Syamsul Azhar Ab Aziz and Khairul Nizam Mohd Kamal - Khairulmaini, Hadi Mukhlis; Ab Aziz, Syamsul Azhar; Mohd Kamal, Khairul Nizam (2006)
The paper focuses on Saddam Hussein's trial in front of the Iraqi High Criminal Court in Baghdad. After providing an overview of the facts surrounding the court's installation, the applicable international law is identified and the fairness and legitimacy of the current proceedings are analyzed. The core on the paper will also take an analytical comparison of the various types of tribunals and trials that have been created to initiate proceedings against similar offences. The paper finishes by considering whether the trial should be relocated and addresses alternative venues that could have been chosen to prosecute Iraq's ex-dictator.